New occurrences of phytotelmata-inhabiting mosquitoes species in northwestern Argentina - Flores, Gabriela Cecilia (2025)
The potential risk areas for emerging or reemerging diseases are determined by the presence, abundance, and distribution of mosquitoes. Here new records and geographical distribution extension of mosquito species in phytotelmata are updated for Argentina. We report for the first time Toxorhynchites bambusicola in Aechmea distichantha in Salta and Tucumán provinces, in the northwest region of Argentina. We also report Anophelesargyritarsis in A. distichantha in Salta province. Culexcoronator, Cx. fernandezi, and Cx.hepperi are reported for the first time from Vriesea friburgensis, a new phytotelma from the northwest region of Tucumán province, Argentina. These findings confirm the need for continued research on mosquito-plant relationships to better understand this complex ecological network and the epidemiological importance of phytotelmata-breeding mosquito species.